2022
DOI: 10.1097/ta.0000000000003847
|View full text |Cite
|
Sign up to set email alerts
|

Timing of venous thromboembolism prophylaxis initiation after injury: Findings from the consensus conference to implement optimal VTE prophylaxis in trauma

Abstract: Optimizing prophylaxis against venous thromboembolic events (VTEs) is a critical issue in the care of injured patients. Although these patients are at significant risk of developing VTE, they also present competing concerns related to exacerbation of bleeding from existing injuries. Especially after high-risk trauma, including injuries to the abdominal solid organs, brain, and spine, trauma providers must delineate the time period in which VTE prophylaxis successfully reduces VTE rates without encouraging blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The WTA defined the timing of early prophylaxis as 12 to 24 h of admission, while the AAST used 48 h as the upper limit [ 4 , 5 ]. A retrospective study measured thrombo-elastography in 304 patients with blunt solid organ injury and found that 13.8% of patients converted to a hypercoagulable state within 48 h [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WTA defined the timing of early prophylaxis as 12 to 24 h of admission, while the AAST used 48 h as the upper limit [ 4 , 5 ]. A retrospective study measured thrombo-elastography in 304 patients with blunt solid organ injury and found that 13.8% of patients converted to a hypercoagulable state within 48 h [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the definition of “early” or “late” VTE prophylaxis may vary depending on the injury type. In cases where there is an ongoing risk of hemorrhage or the injury occurs in a confined space, clinicians must consider the potential consequences of bleeding or hematoma expansion when determining the timing of early VTE prophylaxis [ 20 ]. While the existing literature supports early initiation of pharmacologic VTE prophylaxis for severely injured patients, further prospective studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies that support the safety of early initiation of prophylaxis in patients with solid organ or spinal cord injuries are mainly single center or retrospective. 26,57,58 Summarizing the evidence and discussion from the VTE Consensus Conference, Schellenberg et al 72 present their recommendations for future studies to clarify this knowledge gap.…”
Section: Timing Of Initiation Of Pharmacologic Vte Prophylaxis In Hig...mentioning
confidence: 99%
“…Venous thromboembolism (VTE) prophylaxis with either low-dose unfractionated heparin (UFH) or low molecular weight heparin (LMWH) is recommended for hospitalized trauma patients, with LMWH being preferred for most patients 1–5. Ongoing debate exists regarding the optimal dosing of LMWH, timing of initiation in patients at high risk of hemorrhage, and duration of VTE chemoprophylaxis after discharge 3–18…”
Section: Introductionmentioning
confidence: 99%